2021
DOI: 10.1021/acs.joc.1c01846
|View full text |Cite
|
Sign up to set email alerts
|

Metal- and Solvent-Free Cascade Reaction for the Synthesis of Amino Pyrazole Thioether Derivatives

Abstract: We developed an iodine-mediated cascade strategy to synthesize amino pyrazole thioether derivatives (11) in the absence of metals as well as solvents. The present approach provides amino pyrazole thioethers in a highly selective manner without the formation of diaryl sulfide and sulfenyl-enaminonitrile with broad substrate scope. The reactivity of nine sulfenylation sources and synthetic applications of the synthesized compounds have been demonstrated. Thus, the overall iodine-mediated multicomponent reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Annes et al [85] reported an iodine-mediated three-component reaction of phenylhydazine hydrochloride, a suphenylating source (thiols, thioethers, sulphonylhydrazides, sulphonic acids, sulphonyl chlorides) and 3-aminopropenenitriles for the synthesis of amino pyrazole thioethers 81 selectively (Scheme 40). This one-pot protocol proceeds under neat conditions and shows a broad substrate scope.…”
Section: Synthesis Of Polysubstituted Pyrazolesmentioning
confidence: 99%
“…Annes et al [85] reported an iodine-mediated three-component reaction of phenylhydazine hydrochloride, a suphenylating source (thiols, thioethers, sulphonylhydrazides, sulphonic acids, sulphonyl chlorides) and 3-aminopropenenitriles for the synthesis of amino pyrazole thioethers 81 selectively (Scheme 40). This one-pot protocol proceeds under neat conditions and shows a broad substrate scope.…”
Section: Synthesis Of Polysubstituted Pyrazolesmentioning
confidence: 99%
“…[14] Ramesh's group demonstrated an iodine-mediated cascade strategy for the selective synthesis of aminopyrazole thioether derivatives using phenylhydrazine, thiol, and 3-aminoacrylonitrile as raw materials (Scheme 1d). [15] Wang et.al described an efficient protocol for the synthesis of C-4 sulfenylated pyrazoles via I 2catalyzed domino multicomponent reaction of 1,3-diketones, hydrazines, and thiols (Scheme 1e). [16] Furthermore, Wan et.al developed a rapid approach for the construction of fully substituted pyrazoles via TBAI-catalyzed reaction of 1,3-diketones, sulfonyl hydrazines under TBHP as an oxidant (Scheme 1f).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, iodine‐mediated three‐component [3+2] annulation of β ‐ketonitrile and hydrazides to access richly decorated aminopyrazole thioethers were developed by Tu's and our groups, respectively (Scheme 1c) [14] . Ramesh's group demonstrated an iodine‐mediated cascade strategy for the selective synthesis of aminopyrazole thioether derivatives using phenylhydrazine, thiol, and 3‐ aminoacrylonitrile as raw materials (Scheme 1d) [15] . Wang et.al described an efficient protocol for the synthesis of C‐4 sulfenylated pyrazoles via I 2 ‐catalyzed domino multicomponent reaction of 1,3‐diketones, hydrazines, and thiols (Scheme 1e) [16] .…”
Section: Introductionmentioning
confidence: 99%
“…14 Pharmaceutical, chemical researchers and industries are devoting significant efforts to remove or reduce the volume of hazardous solvents. [15][16][17][18][19] Our lab is focussing on development of green synthetic methods and their applications for preparation of API. 20 We have developed a solvent-free Mannich reaction for preparation of ranitidine, used for treatment of stomach ulcer and acid reflux.…”
mentioning
confidence: 99%
“…, entries[14][15][16][17][18] produced amines with moderate to good yields. Whereas, fluoro substituted ester 1f generated amines with good to excellent yields (Table2, entries 19 and 20).…”
mentioning
confidence: 99%